Caseous Stomatitis Caused by Pseudomonas aeruginosa in Boa constrictor amarali - Martins, Nathana Beatriz; Ferreira, Lucas Arthur Ricardo; Queiroz, Caroline Lopes; Buiatte, Ana Beatriz Garcez; Correia Lima, Anna Monteiro; de Souza, Rafael Rocha; Oliveira, Wilson Junior; Santos, André Luiz Quagliatto (Acta Scientiae Veterinariae, 2021)
Background: Pseudomonas aeruginosa is a bacterium that belongs to the microbiota of snakes, but it may also be an opportunistic pathogen and contaminate humans through fecal contact, bites, and injuries. In snakes, this microorganism may present high pathogenicity at certain conditions and have been associated with high morbidity and mortality. Reports of infection of Boa constrictor by this pathogen are rare. Thus, this study aimed to describe the P. aeruginosa oral infection in a snake specimen (Boa constrictor amarali), approaching the isolation and identification of the infectious agents involved, the antimicrobial sensitivity and resistance, and the therapeutic protocol adopted. Case: A free-living adult female specimen of Boa constrictor amarali (Amaral's boa), with no described previous history was rescued in an urban area by the Environmental Police. Clinical evaluations showed structures of caseous aspect in the oral cavity, with hyperemia spots in the mucosa. Samples of these lesions were sent for mycological examination, and fungal forms were not found. Samples were collected for isolation and culture. The antimicrobial susceptibility of the isolated microorganisms was determined by the modified Kirby-Bauer disk diffusion method. P. aeruginosa was isolated and showed susceptibility to amikacin, gentamicin, and polymyxin-B; intermediate susceptibility to azithromycin, and ciprofloxacin; and resistance to cephalexin, ceftiofur, chloramphenicol, and enrofloxacin. The treatment consisted of cleaning of the oral cavity, local infiltration of lidocaine for debridement of the caseous area that were later cauterized with iodine. Systemic antibiotic therapy was used, with intramuscular administration of amikacin (5 mg/kg) for the first dose and (2.5 mg/kg) for the other doses with intervals of 72 h, and oral administration of metronidazole (20 mg/kg) with intervals of 48 h, both during 21 days. Daily subcutaneous fluid therapy was performed as support treatment, using Lactated Ringer's solution (25 mg/kg) and Vitamin C (10 mg/kg) with intervals of 24 h, being the cure observed at the end of treatment. Discussion: This paper presents the pathological findings of the Pseudomonas aeruginosa oral infection in a B. constrictor amarali. This bacterium is an opportunistic pathogen that is commonly found in snakes, thus, humans in contact with these animals may be contaminated with this pathogen. However, oral cavity lesions associated with P. aeruginosa had not yet been related to Boa constrictor amarali, which is a non-venomous species. Few bacteria associated with reptile diseases are primary causative agents. Clinical bacterial infections generally tend to be secondary to viral infections. Predisposing factors for the development of bacterial diseases in these reptiles include immunodepression, malnutrition, poor adaptation to captivity, and the maintenance of these animals at temperatures and humidities outside their thermal comfort range. In the present study, the P. aeruginosa behaved as an opportunistic pathogen, resulting in clinical manifestations with caseous lesions in the oral cavity, probably due to an imbalance of the microbiota caused by stress or immunodepression. The antibiogram allowed the adoption of a correct therapeutic protocol based on the susceptibility of the pathogen, resulting in remission of lesions and clinical signs after 21 days of treatment.